2021
DOI: 10.7759/cureus.16865
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Minimum Effective Volume of Local Anaesthetic Applied in Brachial Plexus Blockage With an Axillary Approach Under Ultrasonography Guidance?

Abstract: Peripheral nerve blocks with the use of ultrasonography (USG) allow visualisation of both the structures and nerves and make the block administrations safe, quick, and comfortable. However, few publications concerning the minimum local anesthetic (LA) volume are capable of providing blocks. This study aimed to find the minimum effective LA volume in brachial plexus blockage administrations with an axillary approach accompanied by ultrasonography in hand, elbow, and forehand operations. Materials and MethodThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…USG allows direct and real-time visualization of nerve structures, needle position, and LAs and is therefore prevalently used in peripheral nerve blocks. In studies where block implementations have been carried out under USG guidance, the use of USG was associated with lower use of LA, higher block success rates, lower complication rates, and lower opioid consumption [ 6 , 7 ]. In this study, to reduce complication rates and increase the success of the block, USG and NS were used together for guidance.…”
Section: Discussionmentioning
confidence: 99%
“…USG allows direct and real-time visualization of nerve structures, needle position, and LAs and is therefore prevalently used in peripheral nerve blocks. In studies where block implementations have been carried out under USG guidance, the use of USG was associated with lower use of LA, higher block success rates, lower complication rates, and lower opioid consumption [ 6 , 7 ]. In this study, to reduce complication rates and increase the success of the block, USG and NS were used together for guidance.…”
Section: Discussionmentioning
confidence: 99%
“…González et al [10] reported a minimum effective volume of 2% lidocaine with epinephrine 5 µg/mL in 90% of patients for double-injection ultrasound-guided axillary block, 5.5 mL for MC nerve, and 23.5 mL for perivascular injection. Erdogmus et al [9] reported that the volume of 0.5% bupivacaine could decrease by 2.5 mL per nerve for a total of 7.5 mL (radial, ulnar, median nerve block), but decreasing local anesthetic dose will increase onset time and early regression of the block effect. No local anesthetic-related complications were observed in our study.…”
Section: F I G U R E 4 Percentage Of Patients With Motor Paralysis Ac...mentioning
confidence: 99%
“…Various ultrasound injection techniques have been studied to increase the effectiveness of BPB [2,[5][6][7][8]. Ultrasound guidance not only facilitates the anesthetic procedure, but also decreases the dose of local anesthetics [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…If adequate postoperative analgesia is not administered, undesirable consequences such as atelectasis, decreased patient comfort, increased postoperative morbidity, prolonged hospital stay, and chronic pain may be encountered [6,7]. Peripheral nerve blocks are often preferred to prevent postoperative pain due to their low side effects [8]. However, intravenous analgesia is often combined with peripheral blocks to provide more effective analgesia [9].…”
Section: Introductionmentioning
confidence: 99%